Decreased Frequencies of Gamma/Delta T Cells Expressing Th1/Th17 Cytokine, Cytotoxic, and Immune Markers in Latent Tuberculosis-Diabetes/Pre-Diabetes Comorbidity - Kathamuthu, Gokul Raj; Kumar, Nathella Pavan; Moideen, Kadar; Menon, Pradeep A.; Babu, Subash (Frontiers in Cellular and Infection Microbiology, 2021)
Antigen-specific gamma-delta (γδ) T cells are important in exhibiting anti-mycobacterial immunity, but their role in latent tuberculosis (LTB) with diabetes mellitus (DM) or pre-DM (PDM) and non-DM comorbidities have not been studied. Thus, we have studied the baseline, mycobacterial (PPD, WCL), and positive control antigen-stimulated γδ T cells expressing Th1 (IFNγ, TNFα, IL-2) and Th17 (IL-17A, IL-17F, IL-22) cytokine as well as cytotoxic (perforin [PFN], granzyme [GZE B], granulysin [GNLSN]) and immune (GMCSF, PD-1, CD69) markers in LTB (DM, PDM, NDM) comorbidities by flow cytometry. In the unstimulated (UNS) condition, we did not observe any significant difference in the frequencies of γδ T cells expressing Th1 and Th17 cytokine, cytotoxic, and immune markers. In contrast, upon PPD antigen stimulation, the frequencies of γδ T cells expressing Th1 (IFNγ, TNFα) and Th17 (IL-17F, IL-22) cytokine, cytotoxic (PFN, GZE B, GNLSN), and immune (CD69) markers were significantly diminished in LTB DM and/or PDM individuals compared to LTB NDM individuals. Similarly, upon WCL antigen stimulation, the frequencies of γδ T cells expressing Th1 (TNFα) and Th17 (IL-17A, IL-22) cytokine, cytotoxic (PFN), and immune (PD-1, CD69) markers were significantly diminished in LTB DM and/or PDM individuals compared to LTB NDM individuals. Finally, upon P/I stimulation we did not observe any significant difference in the γδ T cell frequencies expressing cytokine, cytotoxic, and immune markers between the study populations. The culture supernatant levels of IFNγ, TNFα, and IL-17A cytokines were significantly increased in LTB DM and PDM after stimulation with Mtb antigens compared to LTB NDM individuals. Therefore, diminished γδ T cells expressing cytokine, cytotoxic, and other immune markers and elevated levels of cytokines in the supernatants is a characteristic feature of LTB PDM/DM co-morbidities.